Spontaneous regression of breast cancer with immune response: a case report - Masahiro Ohara; Yumiko Koi; Tatsunari Sasada; Keiko Kajitani; Seishi Mizuno; Ai Takata; Atsuko Okamoto; Ikuko Nagata; Mie Sumita; Kaita Imachi; Mayumi Watanabe; Yutaka Daimaru; et al. (Surgical Case Reports)
Abstract Background Spontaneous regression (SR) is a rare phenomenon in which a cancer disappears or remits without treatment. We report a case of breast cancer that showed spontaneous tumor regression in the surgical specimen after core needle biopsy. Case presentation A 59-year-old woman came to our hospital complaining of a painful lump in the right breast. In the upper-outer quadrant of the right breast, a tumor with an unclear boundary, 30 mm in diameter, was palpable. In pathological findings from needle biopsy, the tumor was diagnosed as solid-type invasive ductal breast carcinoma. Partial coagulation necrosis was generated in estrogen receptor-negative, HER2-negative, and AE1/AE3-positive ductal carcinoma without infiltration of lymphocytes. Surgery for right breast cancer was then performed. Histological examination of the surgical specimen revealed the tumor was invasive ductal carcinoma with lymphocyte infiltration, coagulation necrosis, and fibrous tissue with hemosiderin. The tumor formed a solid nest, 3 mm in diameter, suggesting the possibility of SR. Conclusions Immune responses, infection, hormones, surgical stress, and ischemia have been reported as mechanisms of SR. The findings in this case strongly suggest that SR of breast cancer is associated with anti-tumor immune responses.